Genetic and Structural Characterization of the Core Region of the Lipopolysaccharide from Serratia marcescens N28b (Serovar O4) - Coderch, Núria (American Society for Microbiology, 2004)
The gene cluster (waa) involved in Serratia marcescens N28b core lipopolysaccharide (LPS) biosynthesis was identified, cloned, and sequenced. Complementation analysis of known waa mutants from Escherichia coli K-12, Salmonella enterica, and Klebsiella pneumoniae led to the identification of five genes coding for products involved in the biosynthesis of a shared inner core structure: [l,d-HeppIIIα(1→7)-l,d-HeppIIα(1→3)-l,d-HeppIα(1→5)-KdopI(4←2)αKdopII] (l,d-Hepp, l-glycero-d-manno-heptopyranose; Kdo, 3-deoxy-d-manno-oct-2-ulosonic acid). Complementation and/or chemical analysis of several nonpolar mutants within the S. marcescens waa gene cluster suggested that in addition, three waa genes were shared by S. marcescens and K. pneumoniae, indicating that the core region of the LPS of S. marcescens and K. pneumoniae possesses additional common features. Chemical and structural analysis of the major oligosaccharide from the core region of LPS of an O-antigen-deficient mutant of S. marcescens N28b as well as complementation analysis led to the following proposed structure: β-Glc-(1→6)-α-Glc-(1→4))-α-d-GlcN-(1→4)-α-d-GalA-[(2←1)-α-d,d-Hep-(2←1)-α-Hep]-(1→3)-α-l,d-Hep[(7←1)-α-l,d-Hep]-(1→3)-α-l,d-Hep-[(4←1)-β-d-Glc]-(1→5)-Kdo. The D configuration of the β-Glc, α-GclN, and α-GalA residues was deduced from genetic data and thus is tentative. Furthermore, other oligosaccharides were identified by ion cyclotron resonance-Fourier-transformed electrospray ionization mass spectrometry, which presumably contained in addition one residue of d-glycero-d-talo-oct-2-ulosonic acid (Ko) or of a hexuronic acid. Several ions were identified that differed from others by a mass of +80 Da, suggesting a nonstoichiometric substitution by a monophosphate residue. However, none of these molecular species could be isolated in substantial amounts and structurally analyzed. On the basis of the structure shown above and the analysis of nonpolar mutants, functions are suggested for the genes involved in core biosynthesis.